ANALISIS PENGARUH MODAL KERJA, MANAJEMEN ASET, DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PT. MITRA SENTOSA ABADI - Winaya Purwanti Winaya Purwanti; Darti Indriyani Darti Indriyani; Henny Risnawati Henny Risnawati (Cakrawala Akuntansi & Manajemen, 2023)
The problem of this research is how the influence of working capital, asset management, and sales growth on profitability at PT. Mitra Sentosa Abadi. So the purpose of this study is to analyze the effect of working capital, asset management, and sales growth on profitability. The research uses multiple linear regression methods and also descriptively to detect any obstacles faced by the company in managing working capital, asset management, sales growth, and profitability. This study used secondary data sourced from the financial statements of a stevedoring company, PT Mitra Sentosa Abadi for the period 2018-2020. The independent variables that are tested in a row are using working capital turnover, total asset turnover, and sales growth ratio, and the dependent variable is a return on asset. The results showed that the working capital variable was negative (-0.001) with a significance value of 0.087 on profitability, asset management was positive (0.653) with a significance value of 0.000 on profitability, and sales growth was negative (-0.003) with a significance value of 0.408 on profitability. The significance value was set at 0.05. This study shows that partially only asset management variables have a positive and significant effect on profitability. Meanwhile, simultaneously the variables of working capital, asset management, and profitability have an effect on profitability with a coefficient of determination (R2) of 0.721. Suggestions and implications for management are to ensure that heavy equipment productivity is aligned with cost efficiency, so the resulting revenue is getting better quality.